In vitro and in silico evaluation of bioactive compounds from Usnea longissima Ach. as antimicrobial agents - Atni, Oky Kusuma; Munir, Erman; Pasaribu, Nursahara; Siregar, Etti Sartina; Saleh, Mohd Nazre (Science Publications, 2026)
Lichens, formed from symbiotic association between of fungi with phototrophic organisms, generate a variety of bioactive chemicals having medicinal potential. This research aimed to examine the antibacterial characteristics of Usnea longissima Ach. using both in vitro and in silico methodologies. The effectiveness of lichen methanol extracts against different diseases was evaluated using the disc diffusion technique. Pathogens included gram-positive, gram-negative, and pathogenic yeast. The extracts showed significant antimicrobial activity, notably inhibiting Propionibacterium acnes (22.3±0.5 mm) and Pseudomonas aeruginosa (18.36±0.33 mm). GC-MS isolated 29 bioactive chemicals, some of which are derivatives of benzoic acid and 9-octadecenal. Lipinski's rule of five was used to provide an assessment of the drug-like properties of these substances. Molecular docking studies with 6KZZ protein, performed using Autodock Vina, revealed high binding affinities for compounds such as 1-propanone (−4.8 kcal/mol) and oxacycloheptadec-8-en-2-one (−5.1 kcal/mol), suggesting their potential as antimicrobial agents. In contrast, compounds including 9-octadecenal (−3.6 kcal/mol) and carbamic acid (−2.8 kcal/mol) showed weaker binding, indicating the need for further optimization. The findings underscore the need for more study into U. longissima as a possible source of new antibiotic compounds.